ANALISIS PROSES DIGITALISASI NASKAH KUNO DI MUSEUM RADYA PUSTAKA: PERAN, STRATEGI, DAN KEBERLANJUTAN PROGRAM - Na’ila Zulfa; Dhiya Inas Izdihar; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
This study aims to examine in depth the stages, obstacles, and sustainability strategies of the ancient manuscript digitization program at Radya Pustaka Museum Surakarta. This research uses a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation studies. The results showed that the role of Radya Pusataka Museum as an ancient manuscript preservation institution. |The process of preserving ancient manuscripts is carried out by digitization by involving the role of human resources and technology. \The process includes manuscript selection, scanning, editing, and storage. However, there are several obstacles such as the physical condition of damaged manuscripts, limited human resources, and technology. The strategy for the sustainability of the digitization program is carried out through setting a priority scale, transliteration and language transfer where the manuscripts that have the most severe damage are prioritized. This research tells us that digitizing ancient manuscripts is not just a technical activity, but a process of preserving cultural identity that must be carried out collaboratively, sustainably, and adaptively to the times.